Effects of pericardiotomy on left ventricular muscle mass and hemodynamic parameters - Kizilay, Mehmet; Yavuz, Senol (Annals of Medical Research, 2021)
Aim: It has been shown in many experimental animal studies that increased myocardial tension and ventricular filling after cardiac pericardiectomy leads to increased myocardial protein synthesis and increased left ventricular muscle mass. In this study, we aimed to show left ventricular muscle mass changes, left ventricular end-systolic-end-diastolic volume changes, significant changes in systolic-diastolic blood pressure and wall stress after pericardiectomy performed in patients with normal ejection fraction undergoing coronary artery bypass graft (CABG) operation.Material and Methods: Echocardiographic ventricular mass, end-diastolic volumes, end-systolic volumes, ejection fraction values were measured in the preoperative 1st day, postoperative 6th weeks and post operative 6th months in our 32 patients with normal ejection fraction who underwent elective coronary artery bypass operation in our clinic. Results: According to the preoperative values, echocardiographic evaluations showed that left ventricular muscle mass index (LVMMI) increased 15% at 6 weeks, %18 at 6 month after CABG operation ( p 0,05). The mean left ventricular end diastolic volume index (LVEDVI) was 55 ±8 ml/m2 preoperatively , 67 ±10 ml/m2 at the 6th week and 70 ±12 ml/m2 at 6th month; this increase was significant respectively (p0.05). This enlargement occurred with no changes in systolic and diastolic blood pressure and did not lead to significant changes in end-systolic volume and end-systolic circumferential wall stress.Conclusion: In conclusion, in patients undergoing coronary artery bypass graft surgery, pericardiectomy may lead to a partial increase in left ventricular end-diastolic volume and left ventricular muscle mass with better left ventricular filling.
Keywords: Left ventricular muscle mass; CABG; pericardiectomy